2018
DOI: 10.1186/s13000-018-0771-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of sessile serrated adenoma/polyps with dysplasia/carcinoma based on immunohistochemistry, next-generation sequencing, and microsatellite instability testing: a case series study

Abstract: BackgroundColorectal sessile serrated adenoma/polyps (SSA/Ps) are considered early precursor lesions in the serrated neoplasia pathway. Recent studies have shown associations of SSA/Ps with lost MLH1 expression, a CpG island methylator phenotype, and BRAF mutations. However, the molecular biological features of SSA/Ps with early neoplastic progression have not yet been fully elucidated, owing to the rarity of cases of SSA/P with advanced histology such as cytologic dysplasia or invasive carcinoma. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 48 publications
(80 reference statements)
5
30
0
Order By: Relevance
“…reported that FBXW7 (a tumor‐suppressor gene) mutant colorectal cancers had significant associations with MSI‐high tumors in a large‐scale study of 1519 cases . Furthermore, MSI‐high SSA/Ps with dysplasia or invasive carcinoma harbored an FBXW7 mutation, indicating that FBXW7 mutations might potentially be involved in the progression of MSI‐high serrated lesions.…”
Section: Molecular Characterization Of Sessile Serrated Adenoma/polypmentioning
confidence: 99%
See 3 more Smart Citations
“…reported that FBXW7 (a tumor‐suppressor gene) mutant colorectal cancers had significant associations with MSI‐high tumors in a large‐scale study of 1519 cases . Furthermore, MSI‐high SSA/Ps with dysplasia or invasive carcinoma harbored an FBXW7 mutation, indicating that FBXW7 mutations might potentially be involved in the progression of MSI‐high serrated lesions.…”
Section: Molecular Characterization Of Sessile Serrated Adenoma/polypmentioning
confidence: 99%
“…Sporadic colorectal cancers with the MSI-high phenotype account for approximately 3-15% of all colorectal cancers. 29 MSI is a unique molecular alteration induced by deficiencies in the DNA-mismatch repair system and is characterized by unstable (variable length) microsatellites, a type of simple DNA 31 Furthermore, MSI-high SSA/Ps with dysplasia or invasive carcinoma harbored an FBXW7 mutation, 16 indicating that FBXW7 mutations might potentially be involved in the progression of MSIhigh serrated lesions. On the contrary, activation of the second arm of the serrated neoplasia pathway, also driven by CpG island methylation of unspecified tumor-suppressor genes but not DNA repair genes, may indicate progression to BRAF-mutant MSS carcinoma.…”
Section: Molecular Characterization Of Sessile Serrated Adenoma/polypmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty studies assessing 3511 serrated adenomas were included . The whole process of study selection is reported schematically in Figure .…”
Section: Resultsmentioning
confidence: 99%